Pengaruh Media Pengaruh Media Pop Up Book Terhadap Motivasi Belajar dan Kemampuan Berpikir Kritis Pada Siswa Kelas IV MIN 1 Serang - Lestari, Dirga Ayu; Farhurohman, Oman (Jurnal keilmuan dan Kependidikan dasar, 2020)
Growing learning motivation and critical thinking is an important thing that can be done early. It is needed as one of the learner ways to face the development of the 21st century in the era of globalization. This can be done through the media to increase the learning motivation and generate the character of critical thinking. Learning media has a function to facilitate teachers in conveying the learning process so that it can generate learning motivation and train the critical thinking skills of learners in solving the problems. The research aims at, (1) explaining the use of media, learning motivation and critical thinking of Fourth Grade Students. (2) knowing the influence of the use of media against the learning motivation of Fourth Grade Students. (3) knowing the influence of the use of media against critical thinking of of Fourth Grade Students. (4) knowing the relation between the use of media against the learning motivation and critical thinking of fourth grade students. The research used quantitative approach of quasi-experimental type with nonequivalent control group-pretest-posttest design. Data analysis in the research was obtained through SPSS 23 program. The results of the research consisted of (1) the use of questionnaire media can provide attention, affection, understanding, that is 23,9%. Learning motivation in experiment class can achieve goal, responsible, feedback, risk, creative and innovative, likes challenge that is 76,36% in good criteria. The control class is 35.8%. high category of critical thinking is 79,16% in experiment class, and the control class is 73,3%. (2) The value of significant is 0.005. Thus, there is a significant influence between the media against learning motivation, with average value of experiment class 33.00 and control class 32.00. (3) The value of significant is 0,000. Thus, there is a significant influence between the media against critical thinking with average value of experiment class 82.5 and control class 78.9. (4) Media correlation coefficient against learning motivation is 0,571 means that it has enough correlation. The media against critical thinking is 0.579 means that it has enough correlation. Thus the pop-up book media has less influence on the motivation of learning and critical thinking, which should be coupled with the model or learning method in the learning process.